2018
DOI: 10.1002/spe.2646
|View full text |Cite
|
Sign up to set email alerts
|

Face detection based on multilayer feed‐forward neural network and Haar features

Abstract: Summary Fast and accurate detection of a facial data is crucial for both face and facial expression recognition systems. These systems include internet protocol video surveillance systems, crime scene photographs systems, and criminals' databases. The aim for this study is both improvement of accuracy and speed. The salient facial features are extracted through Haar techniques. The sizes of the images are reduced by Bessel down‐sampling algorithm. This method preserved the details and perceptual quality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(34 reference statements)
0
6
0
1
Order By: Relevance
“…The Multilayer Perceptron (MLP) network is trained using the backpropagation [ 30 ], which uses data to adjust the network's weights and thresholds to minimize the error in its predictions on the training set. First, it computes the total weighted input x j , using the following equation: where y i is the activity level of the j -th unit in the previous layer and w ij is the weight of the connection between the i -th and the j -th unit.…”
Section: Methodsmentioning
confidence: 99%
“…The Multilayer Perceptron (MLP) network is trained using the backpropagation [ 30 ], which uses data to adjust the network's weights and thresholds to minimize the error in its predictions on the training set. First, it computes the total weighted input x j , using the following equation: where y i is the activity level of the j -th unit in the previous layer and w ij is the weight of the connection between the i -th and the j -th unit.…”
Section: Methodsmentioning
confidence: 99%
“…Face detection is performed on videos having low resolutions ranging from 400*300 to 200*150 for each frame. The frame rate is around 25 fps giving Haar-based face detection an average time of 100ms per frame [ 50 ]. Since super-resolution using the given frames takes an estimated 1s for 7-8 frames, the detection, super-resolution, and recognition rate are selected as 6 fps.…”
Section: Experimental Setup and Analysismentioning
confidence: 99%
“…Ebenezer Owusu et al, 2018 [4] has shown the face detection method using the haar feature extraction and classification by MFNN. His motive for this study was improving its accuracy.…”
Section: Literature Surveymentioning
confidence: 99%